(untitled) (TAJ: Journal of Teachers Association, 2020)
Objective: To describe the clinical presentation and feto-maternal outcome of preterm prelabor rupture of the membrane of patients admitted in a tertiary care hospital of Bangladesh. Methods and Material: This is a cross-sectional observational type study carried out in Rajshahi Medical College Hospital, Rajshahi, Bangladesh during the year 2019 in the Department of Obstetrics and Gynecology. Sixty pregnant women with preterm prelabor rupture of the membrane (gestational age 28 to 37 weeks) were included in this study. Results: The mean age of the women was 27.03±6.13 years. Forty (66.7%) of them were from rural area. Majority were studied up to primary school (33.30%). Sixty five percent were house wife. Thirty seven (61.7%) women were multi gravid. Mean gestational age of the patient was 34.43±2.75 weeks. Antenatal care of the women was low. Most of the women have associated one or more diseases like anemia (35%), Urinary tract infection (28.33%), Pregnancy induced hypertension (20%), Lower genital infection (13.33 %,), gestational diabetes mellitus (10%) and heart disease (3.33%). The mean time interval between membrane rupture and delivery was 29±9 hours. Thirty one patients (51.7%) were delivered by caesarian section. Twenty eight (46.7%) women did not experience any complication and other suffered from wound infection (20%), PPH (10%), puerperal sepsis (8.33%) and chorioamnionitis (11.7%). Mean birth weight of the newborns was 2.16±0.42 Kg. Thirty eight (63.33%) newborn suffered from complications like neonatal asphyxia (30%), respiratory distress syndrome (13.3%), neonatal jaundice (11.7%) and neonatal sepsis (3.3%). Neonatal death was noticed in three (5%) cases. Fetal outcome was found significantly (p< 0.001) associated with low gestational age. Conclusion: Women with low education, associated co-morbidity, long latency and neonate with low birth weight have unfavorable outcome. Antenatal care is an important tool to prevent preterm prelabor rupture of the membrane by identifying the risk factors and its management. Optimum obstetric and medical care is essential for the reduction of these devastating complications. TAJ 2020; 33(2): 1-9